5u+9=109

Simple and best practice solution for 5u+9=109 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5u+9=109 equation:


Simplifying
5u + 9 = 109

Reorder the terms:
9 + 5u = 109

Solving
9 + 5u = 109

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 5u = 109 + -9

Combine like terms: 9 + -9 = 0
0 + 5u = 109 + -9
5u = 109 + -9

Combine like terms: 109 + -9 = 100
5u = 100

Divide each side by '5'.
u = 20

Simplifying
u = 20

See similar equations:

| 9x+5=x-11 | | F(n)=5+3n | | x-.3x=434 | | 2(2y+9)=20 | | 18+18=36 | | 0,1(x-10)-0,6x=1,5x-4 | | p-(p+8)=7(p-4)+3p | | 4(x-2)=9+4x | | 1.2x-3.44= | | 6x+3=2(3x+7) | | 8x-4=3+7x | | (2X-3)(X+4)=13 | | 6=4+2y | | 81.9=33.76+9.1x | | 72+18=16(36) | | 12*6+3(18-10)+5*3-11=x | | -3x-11=3x+13 | | 8x+12=2(4x+6) | | x+38=-14 | | 12c^2-7c-10= | | 0.5(72)+0.25(36)=36 | | -7y+7=35 | | -3(x-7)=18 | | -5=6(3)-27 | | 25x^4-60c^2+36=0 | | 2/x-3=8/3x-3 | | 3=6(-5)-27 | | (12a^2b^-2)/(8a^-3b^7) | | 5x+4=x-20 | | 12a^2b^-2/8a^-3b^7 | | logx=-.29 | | a=84+2(10) |

Equations solver categories